Effectiveness of Emergency Mental Health Promotive Gadget Addiction in Adolescents Using a Mindfulness Attention Awareness Educational Approach - Nove Lestari (Universitas STRADA Indonesia, 2023)
Gadgets among teenagers are a must because sophisticated features can use communication facilities, in the form of messages, entertainment facilities in the form of music, playing games, internet facilities, so gadget technology changes the atmosphere of solitude to become more lively and lively. After counseling, it is hoped that participants will know and apply the management of prevention and handling of mental health emergencies addicted to gadgets. The method used in counseling is the lecture method conducted online or question and answer discussion. The media used in counseling are PPT, leaflets, educational videos, SOP video tutorials for mindfulness exercises and applications to support activities online or online. Based on age, the majority (52.4%) of respondents were 17 years old, the characteristics of the sexes were obtained by the majority (66.7%) of respondents who were female.